Use of Innovative Technologies in the Treatment of Periodontitis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Periodontium (lat. Periodontium) is a complex of tissues located in the fissured space between the cementum of the tooth root and the alveolar plate. Its average width is 0.20-0.25 mm (Wikipedia).The periodontium contains nerves, blood and lymph vessels that supply the tooth. The main functions of the periodontium are trophic (nutrition of the teeth) and shock absorption: when chewing food, the connective tissue absorbs the load on the tooth and distributes it evenly to the bones.